Correction: Anti-biofouling ability and cytocompatibility of the zwitterionic brushes-modified cellulose membrane. Issue 37 (2nd September 2016) - Liu, Pingsheng; Chen, Qiang; Li, Li; Lin, Sicong; Shen, Jian
Abstract : Correction for 'Anti-biofouling ability and cytocompatibility of the zwitterionic brushes-modified cellulose membrane' by Pingsheng Liu et al., J. Mater. Chem. B, 2014, 2, 7222–7231.